La continuïtat µbioliterària» al País Valencià: de Carles Ros a Carles Salvador (o de Gregori Maians a Vicent Andrés Estellés, passant per Teodor Llorente). - RODA, LLUÍS (Scripta)
This article presents evidence of a cultural continuum spanning from the pre-enlightened Valencian Novatores of the late 17th century to the present day. It also highlights the direct cultural connection of València with London and Paris during the first half of the 19th century -along with Cádiz, Madrid or Barcelona, which are more commonly acknowledged. In this context, the Valencian poems µEn los dies del rei Fernando» by Antoni Maria Peyrolon (1830), and µLo somni» by Vicent Salvà (1831) exhibit a high and up to date culture. This paper also evidences the Calasanzian Pious School of València as an early hub of the romantic shift. In 1859, València organized Jocs Florals -Floral Games- in celebration of Ausiàs March. Teodor Llorente, one of the winners, is regarded as the key link that connects the pre-1859 Valencian cultural dignifying efforts and the post-1909 ones. The popular event of Llorente's coronation as Poet in 1909 turned him an icon and concluded the Valencian Renaixença -Rebirth- with a historically sufficient success, as this work proves.